2017
DOI: 10.1158/0008-5472.can-17-0216
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1-Mediated Translation Regulation Is a Crucial Vulnerability of Cancer

Abstract: Through an shRNA screen we identified the protein arginine methyltransferase Prmt1 as a vulnerable intervention point in murine p53/Rb-null osteosarcomas, the human counterpart of which lacks effective therapeutic options. Depletion of Prmt1 in p53-deficient cells impaired tumor initiation and maintenance in vitro and in vivo. Mechanistic studies reveal that translation-associated pathways were enriched for Prmt1 downstream targets, implicating Prmt1 in translation control. In particular, loss of Prmt1 led to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…Recent reports have revealed the relationship between various cancers and PRMT1, which is overexpressed in breast cancer, bladder cancer and lung cancer [17][18][19][20].. Notably, PRMT1 was recently reported to be upregulated through miR-503 in HCC [21], and PRMT1 may promote the proliferation and metastasis of HCC cells in vitro [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have revealed the relationship between various cancers and PRMT1, which is overexpressed in breast cancer, bladder cancer and lung cancer [17][18][19][20].. Notably, PRMT1 was recently reported to be upregulated through miR-503 in HCC [21], and PRMT1 may promote the proliferation and metastasis of HCC cells in vitro [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that histone methylation, a mechanism for modifying chromatin structure, contributes to aberrant transcriptional regulation and oncogenic signaling pathways in osteosarcoma (4). Furthermore, increased expression of histone methyltransferases (HMTs), including G9a, enhancer of zeste homolog 2 (EZH2), nuclear SET domain-containing 3 (NSD3), protein arginine N-methyltransferase 1, and coactivator-associated arginine methyltransferase 1, contribute to osteosarcoma development (5)(6)(7)(8)(9)(10). These data suggested that genes encoding histone methylation modifiers, HMTs and histone demethylases (HDMTs), may serve key roles in the development and progression of OS.…”
Section: Introductionmentioning
confidence: 99%
“…At this juncture, the critical substrates of PRMT1 that mediate AR signaling remain unknown. PRMT1 has a multitude of nuclear and nonnuclear substrates, which vary by cell type and context, and one or more of these may be important for the phenotypes observed herein 53 . For example, PRMT1 can directly modify histone H4 at the R3 position, and the resulting asymmetric dimethyl mark (H4R3me2a) is thought to facilitate transcriptional activation 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…PRMT1 is the primary type I PRMT, accounting for up to 90% of ADMA in cells 56 , though substrate redundancy among PRMTs has been reported 57 . Given the large number of PRMT substrates in the cell 53 , some of which may be cell-essential, toxicity may be limiting with PRMT1 monotherapy. Combination therapy can yield increased durability of response with an expanded therapeutic window, as evidenced, for example, by the success of CDK4/6 inhibitor-endocrine therapy combinations in breast cancer 58 .…”
Section: Discussionmentioning
confidence: 99%